Fatigue life cycle prediction equation based on grain angles and stress levels for Acacia Mangium - William L. N. Buglie; Mohd Shahril Osman (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study aims to investigate and understand the nature of Acacia mangium axial fatigue strengths under repeated stress. Acacia mangium trees, which were cut to produce oven-dried dog bone shaped specimens, were tested in repeated axial-tensile loading with sinusoidal waveform. Findings of this study had shown that Acacia mangium has a significant difference in the strengths parallel and perpendicular to the grain line. Extreme reduction in tensile strength for 0° and 90° grain angles saw a shift from 143.87 MPa to 6.32 MPa (a 95.6% reduction of the Ultimate Tensile Strength). It was observed that the Acacia mangium N-S (Wöhler) plots showed an exponential correlation, in which the N – intercept of the vertical axis was at five (5) million cycles, while the intercept of the horizontal S – axis, was at 143.87 MPa. It was also observed that Acacia mangium has a fatigue endurance limit at 10% of the ultimate tensile strength. From static testing, the Osgood’s coefficient of species for Acacia mangium, (a), was identified algebraically to be 0.49. The finding showed that life cycles predicted by the Fatigue Life Prediction Equation as having almost similar magnitudes with the results defined by the verification test for each stress level. The comparison between the verification test results and the predictions by the equation indicated an impressive fit between them at 30° grain angle.